VD_FINDINFO HC / 2012 / 288 vom 25. April 2012 - VD Tribunal cantonal (2012)
EXPULSION DE LOCATAIRE, BAIL À LOYER, DEMEURE DU DÉBITEUR | 257d CO, 308 al. 2 CPC (CH), 319 let. a CPC (CH), 321 al. 2 CPC (CH)